2017
DOI: 10.1093/femsec/fix076
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microbial communities growing with carbon monoxide, hydrogen, and carbon dioxide

Abstract: Microbial anaerobic conversion of carbon monoxide (CO) and syngas (mainly composed of CO, CO2 and H2) leads to the production of important industrial products, such as acetate and ethanol. The composition of CO- and syngas-converting microbial communities and the microbial interactions involved are still largely unknown. The main objectives of this study were (i) to understand the effects of CO, CO2, and H2 on the structure and function of a CO-consuming microbial community, and (ii) to identify key carboxidot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
1
26
1
1
Order By: Relevance
“…Previous work (Alves et al, ; Guiot et al, ; Luo et al, ) reported that methanogens thrive at low P CO , mainly benefiting from acetate, H 2 , and CO 2 produced from CO, but that they are completely inhibited by the time CO reaches P CO ∼0.3 atm. Higher P CO was required to inhibit methanogens in granular sludge (Sipma et al, ), or after an acclimation period (Esquivel‐Elizondo, Delgado, & Krajmalnik‐Brown, ; Navarro et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work (Alves et al, ; Guiot et al, ; Luo et al, ) reported that methanogens thrive at low P CO , mainly benefiting from acetate, H 2 , and CO 2 produced from CO, but that they are completely inhibited by the time CO reaches P CO ∼0.3 atm. Higher P CO was required to inhibit methanogens in granular sludge (Sipma et al, ), or after an acclimation period (Esquivel‐Elizondo, Delgado, & Krajmalnik‐Brown, ; Navarro et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Other potential carboxidotrophs detected in these experiments were Pleomorphomonas , Blautia , and Oscillospira . Phylotypes most closely associated to Pleomorphomonas , a hydrogenogenic carboxidotroph (Esquivel‐Elizondo, Delgado, & Krajmalnik‐Brown, ) were only detected (up to 3.3%) after the second addition of ethanol (second phase of fermentation) at P CO of 0.08–0.2 atm. This suggests that Pleomorphomonas might have been involved in the fatty acid elongation process, through generation of H 2 :CO 2 , but was inhibited at P CO = 0.3 atm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations